Analisis Kebutuhan Bahan Baku pada Proses Pengolahan Air Bersih di PDAM IPAM Ngagel Surabaya - Fadhil, Laksana; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
The IPAM Ngagel in Surabaya treats water from the Surabaya River using Poly Aluminium Chloride (PAC) for coagulation and chlorine for disinfection. This study identifies the raw material needs for each treatment stage using daily production, chemical usage, and waste data to estimate requirements by the end of 2025. Average production is 4,480.03 L/second. PAC dosage ranges from 25.28–114.55 mg/L, chlorine from 0.96–5.72 mg/L. Estimated PAC needs range from 11,709.02–53,861.47 kg, and chlorine from 468.36–2,810.16 kg. Safety stocks and reorder points vary per unit: Ngagel I (PAC 18,480 kg; chlorine 686 kg), Ngagel II PAC 7,840 kg; chlorine 288 kg, Ngagel III PAC 19,012.5 kg; chlorine 840 kg. For 3-day PAC and 7-day chlorine reserves, Ngagel I needs 47,000–60,000 kg PAC and 3,000–3,750 kg chlorine, Ngagel II 21,500–25,500 kg PAC and 1,400–1,600 kg chlorine, Ngagel III 40,000–60,000 kg PAC and 3,900–5,400 kg chlorine.